EFFECTIVE MICROWAVE SYNTHESIS OF BIOACTIVE THIENO[2,3-d]PYRIMIDINES - Taslimahemad T. Khatri; Viresh H. Shah (Journal of the Chilean Chemical Society, 2017)
A series of novel 2-amino-3-cyanothiophenes (2a-2j) were synthesized using heterogeneous base (K2CO3) supported Gewald reaction. Cyclization of 2a-j with formamide and urea in conventional heating as well as microwave irradiation gave thieno[2,3-d]pyrimidines (3a-3j) and thieno[2,3-d]pyrimidin-2(1H)- ones(4a-4j) respectively. The reaction rates were faster and yields were higher in the microwave conditions. The structures of the compounds were confirmed with elemental analysis, mass spectral analysis, FTIR, 1H NMR and 13C NMR techniques. All the synthesized compounds were subjected to antimicrobial activity (MIC) in vitro by broth dilution method and exhibited a moderate antimicrobial activity.